Analisis Pelaksanaan Pembelajaran PPKn dalam Pembentukan Karakter Siswa SMP Muhammadiyah 1 Makassar - Muhajir Muhajir; Nandri Sugiarti (JED (Jurnal Etika Demokrasi), 2019)
Pancasila education and citizenship is a planned business and is a continuous process. The large number of shifts in the lives of Indonesian students is currently a very important problem for education in Indonesia. This study aims to: (1) analyze the implementation of PPKn learning in student character formation, and (2) find out the challenges faced by PPKn teachers in forming the character of students of Makassar 1 Muhammadiyah Middle School. This research is a descriptive qualitative study. Data source samples were taken using Purposive sampling technique. Research variables include the implementation of PPKn learning and student character. Data collection techniques using interviews, documentation, and observation. The results of the study indicate that First, the implementation of PPKn learning carried out by the teacher in the class has included character values; Second, the factors that inhibit character formation are students 'lack of understanding of character, lack of PPKn lesson hours, and students' self awareness; Third, how to minimize obstacles, namely to provide understanding and examples to students about character values, increase PPKn lesson hours in schools, and foster awareness in students about the importance of character.Keywords : Learning Implementation, PPKn, Student Character.